Pengaruh Amortisasi Goodwill terhadap Kegunaan Informasi Laba pada Perusahaan Manufaktur - Erni Suryandari; Putria Yunitha (Journal of Accounting and Investment, 2011)
The purpose of this study is to examine the usefulness of earnings and goodwill amortization by comparing the earnings before goodwill and the reported earnings (which include goodwill amortization). In addition, this study also investigates whether goodwill amortization contains incremental value-relevant information. We use 25 firm-year observations selected purposively from 2001 to 2008 of all listed companies in Bursa Efek Indonesia (BEI) that report goodwill, as our sample. We find that earnings before goodwill amortization does not explain significantly more of the observed distribution of share prices than do earnings after goodwill amortization. Our result suggest that goodwill amortization contain incremental value-relevant information. In other words, it have any unique contribution in the relation between earnings and share velue.